Cytotoxic Dammarane-Type Triterpenoids from Aglaia cucullata Peel Fruit - Intan Hawina Anjari; Desi Harneti; Kindi Farabi; Al Arofatus Naini; Ace Tatang Hidayat; Risyandi Anwar; Hadi Kuncoro; Mohamad Nurul Azmi; Unang Supratman (Universitas Gadjah Mada, 2024)
Four triterpenoids, known as dammarane-type, dammaradienone (1), 20(S),25-epoxy-5α-dammar-20-en-3-one (2), 20(S)-5α-dammar-24-en-3α,20-diol-3-acetate (3) and 3α-acetyl-20S,24S-epoxy-25-hydroxydammarane (4), were isolated from Aglaia cucullata peel fruit. The structures of isolated compounds were identified based on their HR-TOFMS data and extensive NMR spectroscopic analysis, as well as compared with literature data. Compounds 1-4 were assessed for cytotoxic effects against HeLa cervical and B16-F10 melanoma skin cancer cells. All compounds showed moderate to weak activity against B16-F10 cancer cells, while compound 2 exhibited the strongest activity against HeLa cancer cells with IC50 of 7.10 µg/mL indicating that the existence of an epoxy moiety at the side chain increases the cytotoxicity to HeLa cells.